Methods of cognitive function investigation in the Longitudinal Study on Adult Health (ELSA-Brasil) - Passos, Valéria Maria de Azeredo; Caramelli, Paulo; Benseñor, Isabella; Giatti, Luana; Barreto, Sandhi Maria (São Paulo Medical Journal, 2014)
CONTEXT AND OBJECTIVE: Many uncertainties concerning risk factors and evolution of cognitive disorders remain. We describe the methods and preliminary results from the investigation of the cognitive function in the Longitudinal Study on Adult Health (ELSA-Brasil). DESIGN AND SETTING: Multicenter cohort study on public employees at six public teaching and research institutions. METHODS: The participants were interviewed and examined to obtain a broad range of social, clinical and environmental characteristics. The following standardized tools were used to assess memory, language and visuospatial and executive functions: words or figure memory test; semantic (animals) and phonemic (letter F) verbal fluency tests; and trail test B. RESULTS: 15,101 out of 15,105 participants took the cognitive tests: 54% were women; the mean age was 51 years; and 52% had a university degree. 14,965 participants (99%) did the word test and 136 (1%) did the figure test due to low schooling level. The scores from the semantic verbal fluency tests (mean = 18.42 ± 5.29; median = 18 words) were greater than the scores from the phonemic verbal fluency tests (mean = 12.46 ± 4.5; median = 12 words). The median time taken to perform the trail test was 1.6 minutes. CONCLUSION: The large cohort size, of young age, and the extensive amount of clinical and epidemiological data available will make it possible to investigate the prognostic value of biological, behavioral, environmental, occupational and psychosocial variables over the short and medium terms in relation to cognitive decline, among adults and elderly people.